2016
DOI: 10.3847/0004-6256/152/6/196
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Abundances in Cool Stars

Abstract: Chlorine abundances are reported in 15 evolved giants and one M dwarf in the solar neighborhood. The Cl abundance was measured using the vibration-rotation 1-0 P8 line of H 35 Cl at 3.69851 µm. The high resolution L-band spectra were observed using the Phoenix infrared spectrometer on the Kitt Peak Mayall 4m telescope. The average [ 35 Cl/Fe] abundance in stars with -0.72<[Fe/H]<0.20 is [ 35 Cl/Fe]=(-0.10±0.15) dex. The mean difference between the [ 35 Cl/Fe] ratios measured in our stars and chemical evolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 64 publications
(82 reference statements)
5
19
0
Order By: Relevance
“…Adopting these temperatures, the column densities of Na 37 Cl needed to reproduce the observed Na 37 Cl ( v =0, J =26-25) profile are between ~2×10 14 and 5×10 14 cm −2 , comparable to the column densities of NaCl found in VY CMa and IK Tau (Milam et al 2007). While our crude estimate has large errorbars, this agreement suggests that our order-of-magnitude value is roughly correct, since the 35 Cl/ 37 Cl isotope ratio is known to be low, about two, in intermediate-mass AGB stars (e.g., Maas et al 2016; Highberger et al 2003, and references therein).…”
Section: Discussionsupporting
confidence: 54%
“…Adopting these temperatures, the column densities of Na 37 Cl needed to reproduce the observed Na 37 Cl ( v =0, J =26-25) profile are between ~2×10 14 and 5×10 14 cm −2 , comparable to the column densities of NaCl found in VY CMa and IK Tau (Milam et al 2007). While our crude estimate has large errorbars, this agreement suggests that our order-of-magnitude value is roughly correct, since the 35 Cl/ 37 Cl isotope ratio is known to be low, about two, in intermediate-mass AGB stars (e.g., Maas et al 2016; Highberger et al 2003, and references therein).…”
Section: Discussionsupporting
confidence: 54%
“…Esteban et al (2015) and Henry et al (2004) found a weak trend towards decreasing Cl abundance with galactic radius, based on data from Hii regions and planetary nebulae (PNe). They also found very similar relations between Cl and O gradients with galactic radius, suggesting that the production of Cl and O are correlated (Maas et al 2016;Maas & Pilachowski 2021) and hence that Cl can be used as a tracer of metallicity. From a study of PNe, Delgado-Inglada et al (2015) found that Cl is a good indicator of metallicity in the progenitors of PNe (i.e., AGB stars).…”
Section: Chlorine Abundance and Isotopic Ratiomentioning
confidence: 80%
“…From a study of PNe, Delgado-Inglada et al (2015) found that Cl is a good indicator of metallicity in the progenitors of PNe (i.e., AGB stars). Hence, the comparison of an AGB Cl abundance with the solar abundance might indicate a higher or lower metallicity of the natal environment of the AGB star, without obfuscation from elements actively synthesised by AGB stars (which 35 Cl is not, based on the investigation of Maas et al 2016). However, the solar abundance of chlorine is very difficult to measure, for reasons discussed in detail by Maas et al (2016).…”
Section: Chlorine Abundance and Isotopic Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to F, the photospheric Cl abundance can only be estimated from sunspot spectra since the HCl molecule requires cool temperatures; no atomic features of Cl are present in the solar spectrum. Recently, Maas et al (2016) revisited the previous HCl sunspot study of Hall & Noyes (1972) with improved molecular data and observations to obtain a 0.19 dex lower abundance: log Cl = 5.31 ± 0.12. Given the remaining model challenges, especially in finding a suitable model atmosphere for a sunspot of unknown T eff , we argue that the quoted uncertainty is likely overly optimistic, and we instead adopt ±0.20 dex.…”
Section: The Heavy Elements: Copper To Uraniummentioning
confidence: 99%